Prednisone for chronic active liver disease: dose titration, standard dose, and combination with azathioprine compared. Issue 11 (November 1975) - Summerskill, W H; Korman, M G; Ammon, H V; Baggenstoss, A H
Abstract : Among 120 consecutive patients with chronic active liver disease (CALD) randomized to different treatments, those receiving maintenance doses of prednisone 20 mg daily (Pred), prednisone in doses given on alternate days and titrated to secure resolution of clinical and biochemical abnormalities (Pred-Titrad), or a combination of prednisone 10 mg and azathioprine 50 mg daily (Comb) survived and underwent resolution of clinical and biochemical features of disease more often than a control group receiving placebo or azathioprine 100 mg daily. Histological remission occurred significantly more often with Pred and Comb than with other regimens. Major side-effects of therapy were commoner with Pred than with Comb or Pred-Titrad, which did not differ. We conclude that Comb is the initial treatment of choice for CALD, since clinical, biochemical, and histological resolution of disease activity occurs as often as with Pred, whereas early side-effects are significantly less frequent.